Why the Bias within Ukraine towards Forced Emigrants in the EU is Debatable and Risky - Taras Romashchenko (Current Issues in Migration Research, 2025)
The Russian aggression forced millions of Ukrainians to flee their homes in search of safety outside Ukraine. Europe took most of the refugees – 6.3 million out of almost 7 million recorded globally. In this context, the return of millions of refugees to Ukraine will largely determine its socio-economic recovery in the post-war era. However, re-emigration en masse may be challenged due to the growing tension within Ukrainian society with those in Ukraine making intolerant remarks about compatriots abroad. Hence, the article points to media examples of bias towards Ukrainian forced migrants on the part of the general public and authorities. It is argued that such attitudes are often groundless and may also have adverse implications for the future return of Ukrainian refugees and upcoming reconstruction of the war-torn country. It is emphasised that the government should mitigate such tension between Ukrainians in and outside Ukraine by all available means. Otherwise, millions of Ukrainians may remain in exile even after the end of hostilities.
Keywords: 300; forced migrants; refugees; biased approach; return migration; Ukraine